2018
DOI: 10.1111/joca.12233
|View full text |Cite
|
Sign up to set email alerts
|

How Does Consumers' Financial Vulnerability Relate to Positive and Negative Financial Outcomes? The Mediating Role of Individual Psychological Characteristics

Abstract: Vulnerable consumers are at particular risk of financial detriment due to, for example, low financial literacy or numeracy, high debt, low income, or impactful changes in personal circumstances. We introduce a comprehensive and formative measure of financial vulnerability that integrates these risk factors and is grounded in definitions of vulnerability from financial regulation bodies and government agencies such as the Consumer Financial Protection Bureau. Across three studies of US individuals, we assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(68 citation statements)
references
References 86 publications
(137 reference statements)
2
66
0
Order By: Relevance
“…Accordingly, a sense of agency over one's life outcomes is valuable in engaging in beneficial behaviors across different domains of daily decision‐making. This finding extends work showing the importance of self‐efficacy in individuals' ability to cope with economic risks (Engelberg, 2007), and work showing the importance of individuals' self‐assuredness or “self‐belief” in their capabilities to explain their engagement in positive financial behaviors (e.g., Farrell et al ., 2016; Hoffmann and McNair, 2019).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, a sense of agency over one's life outcomes is valuable in engaging in beneficial behaviors across different domains of daily decision‐making. This finding extends work showing the importance of self‐efficacy in individuals' ability to cope with economic risks (Engelberg, 2007), and work showing the importance of individuals' self‐assuredness or “self‐belief” in their capabilities to explain their engagement in positive financial behaviors (e.g., Farrell et al ., 2016; Hoffmann and McNair, 2019).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Recent work suggests that psychological variables can offer novel insights to guide policy interventions, such as in the context of poverty alleviation (e.g., Haushofer and Fehr, 2014) and when supporting financially vulnerable individuals (Hoffmann and McNair, 2019). Furthermore, policymakers in the U.S. (CFPB, 2013) as well as the U.K. (Money Advice Service, 2015) stress the role of psychological characteristics in better understanding individuals' financial capability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second aim of our study is to test whether visual attention focused on positive or negative aspects of debt, numerical literacy, graph literacy, and linguistic literacy moderates the effectiveness of financial education. Previous studies have shown that these factors may play an important role in learning effectiveness and in financial literacy acquisition (Banks and Oldfield, 2007 ; Okan et al, 2016 ; Hoffmann and McNair, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consumer vulnerability is commonly conceptualized as a state of powerlessness, which arises from an interaction of individual characteristics (e.g., age, health, cognitive capacity, socioeconomic status); individual states (e.g., life transitions), and external conditions (e.g., discrimination) (Baker et al ., 2005). Vulnerable consumers have also been referred to as “at‐risk consumers,” with limited ability to engage in a marketplace (Hoffmann and McNair, 2018). Zooming in the consumer vulnerability among internal migrant workers in China with a focus on consumer resilience, this research initiates a much‐needed discussion on the process of well‐being production among vulnerable consumers.…”
mentioning
confidence: 99%